Case Report: Post-hip tuberculosis surgery: a rare case of giant iliac intraosseous epidermoid cyst - Wei, Guo; Liang, Jie (Frontiers in Oncology, 2025)
BackgroundIntraosseous epidermoid cyst (IEC) is a rare, non-neoplastic benign lesion. Acquired IECs are extremely rare and are predominantly attributed to trauma or iatrogenic interventions. The present case pertains to an iliac bone epidermoid cyst that emerged subsequent to surgery for hip joint tuberculosis, and to date, no corresponding documentation has been recorded in the extant literature.Case summaryA 43-year-old female, who had undergone an operative intervention for right hip joint tuberculosis 35 years ago, presented with a one-year history of activity-induced pain in the right hip. The radiographs revealed a narrowed joint space of the right hip joint, a shortened femoral neck, ischemic necrosis of the femoral head, and a large expansile radiolucent lesion with cortical erosion in the right iliac bone. Computed tomography (CT) demonstrated significant osteolytic destruction in the right iliac wing, along with a mass in the surrounding tissue. The patient underwent biopsy confirming the diagnosis of an IEC. She was successfully treated with curettage and allogeneic bone grafting.ConclusionDespite the extreme rarity of this event, we should be aware of the potential de novo development of epidermoid cyst in patients who underwent surgery in the pelvic region, especially those related to surgery for hip joint tuberculosis. Once the diagnosis is made, thorough intra-lesional curettage with bone graft can achieve better postoperative outcomes.